Сором і вина як фрагменти емотивної картини світу (на матеріалі української фраземіки) - Zahnitko, Anatoliy; Krasnobayeva-Chorna, Zhanna (Przegląd Wschodnioeuropejski, 2022)
The article belongs to the series of publications devoted to the investigation of fundamental human emotions representated in Ukrainian phrasal verbs. The article examines the psychophysiological patterns of emotions of shame and guilt in Ukrainian phraseology. The subject of the article includes denotation phrases of shame and guilt in the Ukrainian language. A parametric analysis of the semantic structure of the phrase is used as the main method. In Ukrainian phraseology, the studies of the pantomimic expressions of shame and guilt are consistent with cross-cultural explorations and descriptions of fundamental human emotions actualized in kinesthetic phrases. Vegetative body reactions to shame are represented by heat and redness. The eyes, face and body are the main non-verbal indicators of shame and guilt. However, the loci of shame are the soul and the heart. In the Ukrainian culture, there is a connection between shame and public opinion and reputation. Shame and guilt threaten with a potential loss of reputation. The emotion of guilt is also predicated by the intention to ‘scapegoating’ and marked by negative concepts (swamp, dirt, mud, sludge).